Payment for Environmental Services and Polder Sustainable Management in the Context for Poverty Reduction in Semarang - SANTOSO, EDI; HADI, SHUDARTO P; WARELLA, WARELLA (Jurnal Studi Pemerintahan, 2013)
Environmental issues are externalities of economicdevelopment requires the handling of various instrumentsin order to be in harmony with the eco-nomicdevelopment environment. Payment for Envi-ronmentalServices (PES) is now being developed globally as amarket-based instrument that is prom-ising to addressthe issue of degradation of natural resources and theenvironment. PES mechanism has to be said that theconcept is simple and flexible in a variety of conditions,so that the application was highly variable throughoutthe world. The main prob-lem lies in whether thePayment for Environmental Services (PES) that is nowbeing developed globally as a market-based instrumentsare quite capable of dealing with poverty anddegradation of natural re-sources and the environment.Refer to research find-ing shows that Tawang Polderhas significant direct and indirect value for society.About 50% house-hold stated that they accept PES and20% who re-ject the PES. Even PES is quiet potential inreducing poverty in these areas. Even in the societylevel such as huge support in Polder systems, socialcapital and local wisdom, the system management ofpolder should be designed appropriately and have to increasethe level of participation in decision making.Another factor is also important is polder institutionwhich has to be design clearly and transparent based onperformance standart. The last factor is politic capitalshould be aware of democratization.Keywords : Environtmental Management, PovertyReduction, Polder System